2014
DOI: 10.1016/j.ecoenv.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation and dermal exposure to atmospheric polycyclic aromatic hydrocarbons and associated carcinogenic risks in a relatively small city

Abstract: a b s t r a c tThe aim of this study was to conduct a carcinogenic risk assessment for exposure to polycyclic aromatic hydrocarbons (PAHs) via routes of inhalation and dermal contact. Concentrations of 19 PAH species were determined during a heating period at a site in the city of Balikesir, Turkey. Two questionnaires were administered to a sample of inhabitants to determine time-activity budgets and demographic information. The assessment was conducted for each participant and Balikesir population by determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Gaga et al (2012) reported average inhalation risks for heating (2.92 × 10 −3 ) and non-heating periods (1.15 × 10 −3 ) in Kocaeli. Gungormus et al (2014) estimated inhalation risk as 4.12 × 10 −5 and dermal risk as 1.63 × 10 −6 in Balikesir, a relatively small city.…”
Section: Responsible Editor: Constantini Samaramentioning
confidence: 98%
See 1 more Smart Citation
“…Gaga et al (2012) reported average inhalation risks for heating (2.92 × 10 −3 ) and non-heating periods (1.15 × 10 −3 ) in Kocaeli. Gungormus et al (2014) estimated inhalation risk as 4.12 × 10 −5 and dermal risk as 1.63 × 10 −6 in Balikesir, a relatively small city.…”
Section: Responsible Editor: Constantini Samaramentioning
confidence: 98%
“…Risk associated with inhalation route was 1.83-4.20 times higher than the dermal route in Spain (Vilavert et al 2014). The only study considering both of the exposure routes for assessment in Turkey was conducted by Gungormus et al (2014) in Balikesir, a relatively small city with a population of about 266,000. The population risks associated with inhalation exposure ranged between 1.32 × 10 −7 and 2.23 × 10 −4 by using the same SF value used in this study.…”
Section: Exposure and Risk Assessmentmentioning
confidence: 99%
“…where C j is the BaP equivalents (BaP eq ) for each PAH compound concentration (ng/m 3 ) or the concentration of 2,3,7,8-tetrachlorodibenzo-pdioxin equivalents for each dioxin-like PCB congener (pg/m 3 ) or concentration of each non-dioxin like PCB congener (pg/m 3 ), IR is inhalation rate (m 3 /day), ED is exposure duration (yr), EF is exposure frequency (days/yr), BW is body weight (kg), and AT is averaging time that is assumed as lifetime (25,550 days) in carcinogenic risk assessment. Toxic equivalence factor (TEF) values proposed by Nisbet and LaGoy (1992) Kavcar et al (2006), Yılmaz Civan (2010), Gungormus et al (2014), andYılmaz Civan et al (2015). They reported overall IR and BW probability distributions.…”
Section: Exposure and Risk Assessmentmentioning
confidence: 99%
“…CRPF approach could be used for estimation of the cumulative cancer risk of DBP mixture, dividing the DBP components to subclasses and selecting an index component for each subclass. Their doses are converted to index chemical equivalents using the RPFs, similar to Toxic Equivalency Factors that have been used for pollutants such as polycyclic aromatic hydrocarbons, dioxins, and dioxin-like polychlorinated biphenyls (Gungormus et al, 2014;Ugranli et al, 2016;Dumanoglu et al, 2017;Cetin et al, 2018). Then, the risk factor of the index chemical is used to calculate the risk associated with the calculated total dose of the subclass.…”
Section: Introductionmentioning
confidence: 99%